Big Data in Public Policy Making: Challenges and Opportunities in Indonesia - Sukand, Gayatri (Politeknik Siber Cerdika Internasional, 2024)
The integration of Big Data in public policy making presents both significant challenges and promising opportunities for governance in Indonesia. This article explores the potential of Big Data to enhance decision-making processes, optimize resource allocation, and increase policy responsiveness to societal needs. Key challenges identified include issues of data quality, privacy concerns, and the complexities of integrating diverse data sources within existing policy frameworks. Additionally, the capacity of government institutions to effectively interpret and utilize Big Data remains limited due to technological and human resource constraints. On the other hand, the opportunities offered by Big Data, such as predictive analytics and real-time monitoring, have the potential to revolutionize policy formulation and implementation. By examining case studies and analyzing recent developments, this article provides a comprehensive overview of how Big Data can contribute to more transparent, inclusive, and evidence-based public policies in Indonesia. Recommendations for addressing existing challenges and fostering a conducive environment for Big Data utilization are also discussed.